Catalyst rich in PtZn-ZnOx interfacial active sites for producing benzoic acid at low potential as well as preparation method and application of catalyst

By developing catalysts rich in PtZn-ZnOx interface active sites, the problem that existing catalysts require high oxidation potential in benzyl alcohol oxidation reaction is solved, and a highly efficient catalytic oxidation reaction at low potential is achieved, with high selectivity and good cycling stability.

CN119913563AActive Publication Date: 2025-05-02SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411994785.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing catalysts require a higher oxidation potential in the benzyl alcohol oxidation reaction, resulting in high energy consumption and frequent side reactions, making it difficult to achieve efficient and low-energy consumption biomass conversion.

Method used

A catalyst rich in PtZn-ZnOx interfacial active sites was developed, prepared by impregnation method and H2 reduction method, with a body-center cubic structure and rich interfacial active sites, which can efficiently catalyze oxidation reaction at low potentials.

Benefits of technology

It has achieved efficient catalytic oxidation of benzyl alcohol at low potential (<0.9V), high product selectivity, electrocatalytic Faraday efficiency reaches 100%, and has good cycle stability and universality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913563A_ABST
    Figure CN119913563A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst rich in PtZn-ZnOx interfacial active sites for low-potential benzoic acid production and a preparation method and application thereof.The catalyst has a PtZn intermetallic compound structure, the surface of the catalyst is provided with rich PtZn-ZnOx interfaces, and biomass-derived alcohol small organic molecules can be remarkably promoted to generate a PtZn-ZnOx interface active sites under the low potential; 0.9 V, relative to a reversible hydrogen electrode). The PtZn-ZnOx catalyst is applied to electro-catalysis benzyl alcohol oxidation reaction, benzyl alcohol can be subjected to electro-catalysis oxidation into benzoic acid at the selectivity of 99.5% under the low potential of 0.725 V, the electro-catalysis Faraday efficiency can reach 100%, and high conversion efficiency and excellent product selectivity are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanotechnology and biomass conversion electrocatalysis technology, and particularly relates to a PtZn-ZnO-rich catalyst for low-potential benzoic acid production. x Catalysts with interfacial active sites, and preparation methods and applications thereof. Background Art

[0002] Biomass value-added driven by renewable energy plays a vital role in achieving energy storage and the production of renewable fine chemicals. Among them, hydroxyl-rich alcohol organic small molecules (such as methanol, benzyl alcohol, ethanol, ethylene glycol, glycerol, furfuryl alcohol, glucose, lignin, etc.) are an important class of biomass derivatives, and their value-added products have been widely studied and applied in the fields of energy raw materials and chemical production. Taking biomass-derived benzyl alcohol (Ph-CH2OH) as an example, it has significant application potential because it can be effectively converted into high-value benzoic acid (Ph-COOH). Its product benzoic acid, as an important value-added chemical, is widely used in synthetic fibers, resins and anti-corrosion industries, and is a basic intermediate for many chemical products.

[0003] Traditionally, the industrial production of benzoic acid mainly relies on the toluene oxidation process, which usually requires high temperature (140℃ to 160℃), high pressure (0.2MPa to 0.3MPa), and the use of chemical additives such as potassium permanganate (KMnO4), acidic solvents, and bromide promoters. This process not only has harsh reaction conditions, but also is accompanied by complex purification operations (such as distillation and recrystallization), which ultimately leads to high carbon emissions. More environmentally friendly and efficient alternative methods are urgently needed. In recent years, the use of electrocatalytic methods to carry out benzyl alcohol oxidation (BAOR) using water as an oxygen source at room temperature has become a promising alternative for the synthesis of benzoic acid. Compared with traditional aerobic oxidation and photocatalytic oxidation methods, electrocatalytic BAOR has many advantages such as mild reaction conditions, higher product purity, simplified separation and purification process, and higher catalyst recovery rate. More importantly, electrocatalytic BAOR involves only two oxidation products and has been proven to be an ideal system for simplifying complex reaction networks and studying the CH bond activation mechanism. This simplified reaction model provides a new research perspective for improving the conversion efficiency of biomass raw materials (such as alcohols, furfural, glycerol, etc.) and understanding their reaction mechanisms, especially for the conversion process of these basic chemical components.

[0004] At present, the electrocatalytic oxidation of biomass-derived alcohols, such as benzyl alcohol, usually requires a high oxidation potential, which leads to a large voltage input and energy consumption. In order to improve the selectivity and efficiency of the benzyl alcohol oxidation reaction, researchers have carried out a lot of work, especially by developing new electrode materials to optimize the reaction performance. Transition metal oxides and hydroxides (such as nickel and cobalt-based catalysts) have been widely studied and show good catalytic performance. On these catalysts, electrocatalytic BAOR usually follows a nucleophilic oxidation reaction mechanism, which requires the generation of high-valent active metals at high oxidation potentials (>1.3V) and their reduction to a lower oxidation state by nucleophiles (such as benzyl alcohol). Nevertheless, reactions at high voltages still lead to high energy consumption and may trigger competing side reactions, such as oxygen evolution reactions or dissolution and decay of electrode materials. (References: Energy Environ. Sci. 2020, 13(12), 4990-4999; Adv. Funct. Mater. 2023, 34(11), 2311611; ACS Catal. 2023, 13(7), 4272-4282) Therefore, it is of great practical significance to develop electrocatalysts with high current density, low oxidation potential (<0.9V, relative to the reversible hydrogen electrode), high reaction rate, good stability, low cost, energy saving and environmental protection, and catalysts and catalytic methods for biomass conversion and electrocatalytic selective oxidation of biomass-derived alcohol organic small molecules. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the existing catalyst has a high working potential, and propose a PtZn-ZnO-rich catalyst for producing benzoic acid at a low potential. x A catalyst with interfacial active sites, a preparation method and an application thereof. The catalyst has a high catalytic oxidation reaction rate at a low potential (<0.9V) and a high selectivity for benzoic acid products, and can be extended to other biomass-derived alcohol organic small molecules.

[0006] The present invention solves the technical problem by adopting the following technical solutions:

[0007] A PtZn-ZnO-rich catalyst for low-potential production of benzoic acid x A method for preparing a catalyst with interfacial active sites comprises the following steps:

[0008] (1) taking zinc oxide powder and immersing it in a precursor solution containing platinum ions to obtain a zinc oxide composite that adsorbs platinum ions;

[0009] (2) dispersing the complex described in step (1) in a tris(hydroxymethyl)aminomethane solution, adding dopamine hydrochloride, and performing a mechanical stirring reaction;

[0010] (3) obtaining a composite sample coated with a polydopamine layer through filtering, washing, centrifuging and drying;

[0011] (4) placing the composite sample of step (3) in a tube furnace for high-temperature reduction reaction, cooling to room temperature after reduction, and obtaining a PtZn intermetallic compound supported on nitrogen-doped carbon;

[0012] (5) exposing the PtZn intermetallic compound described in step (4) to air aging to obtain PtZn-ZnO x catalyst.

[0013] Furthermore, in step (1), the mass volume ratio of the zinc oxide to the precursor solution containing platinum ions is 25 to 400 mg / mL.

[0014] Preferably, the mass volume ratio of zinc oxide to the precursor solution containing platinum ions in step (1) is 160 mg / mL.

[0015] Furthermore, the precursor solution of platinum ions in step (1) is one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, platinum chloride, platinum acetylacetonate, and tetraammineplatinum nitrate, and the concentration of the precursor solution containing platinum ions is 0.05 to 0.3 g / mL.

[0016] Preferably, the precursor solution containing platinum ions in step (1) is chloroplatinic acid, and the concentration of the precursor solution containing platinum ions is 0.1 g / mL.

[0017] Furthermore, the impregnation process in step (1) is as follows: the zinc oxide powder and the precursor solution containing platinum ions are fully mixed and then immersed at room temperature for 12 to 48 hours until completely dried.

[0018] Preferably, the immersion time in step (1) is 24 hours.

[0019] Furthermore, the concentration of the tris(hydroxymethyl)aminomethane solution in step (2) is 5 to 20 mmol / L; and the mass ratio of dopamine hydrochloride to zinc oxide powder in step (2) is 0.1 to 3.

[0020] Preferably, the concentration of the tris(hydroxymethyl)aminomethane solution in step (2) is 10 mmol / L; and the mass ratio of dopamine hydrochloride to zinc oxide powder in step (2) is 0.5.

[0021] Furthermore, the dispersion process in step (2) includes ultrasonic mixing and stirring mixing; and the mechanical stirring reaction duration in step (2) is 8 to 24 hours.

[0022] Furthermore, the washing solvent used in step (3) is one of deionized water, anhydrous ethanol and a mixture thereof; the centrifugal speed in step (3) is 5000-10000 rpm, the number of centrifugation is 1 to 3 times, and the time of each centrifugation is 2 to 5 minutes; the drying method in step (3) is oven drying at 60 to 80°C.

[0023] Furthermore, the conditions for the high-temperature reduction reaction in step (4) are: a hydrogen-argon mixed gas as a protective atmosphere, wherein the hydrogen gas volume fraction is 5-10%, the temperature is increased to 600-800°C at a heating rate of 5-10°C / min and maintained for 0.5-2 hours.

[0024] Preferably, the conditions for the high-temperature reduction reaction in step (4) are: a hydrogen-argon mixed gas as a protective atmosphere, wherein the hydrogen gas volume fraction is 5%, and the temperature is increased to 800° C. at a heating rate of 5° C. / min and maintained for 1 hour.

[0025] Furthermore, the aging conditions in step (5) are: exposure to air at room temperature for 1 to 10 hours.

[0026] The present invention provides a PtZn-ZnO-rich catalyst for low-potential benzoic acid production prepared by the above-mentioned preparation method. x The catalyst has a PtZn intermetallic compound structure, a body-centered cubic (bcc) structure, and has abundant PtZn-ZnO x interface.

[0027] The PtZn-ZnO rich in PtZn-ZnO prepared by the above method for low potential production of benzoic acid x Catalysts with interfacial active sites can be used for the low-potential (<0.9V) oxidation of organic compounds such as benzyl alcohol, methanol, ethanol, ethylene glycol, glycerol, isopropanol, diethylene glycol, furfuryl alcohol, 5-hydroxymethylfurfural, and 4-hydroxy-3-methoxybenzyl alcohol at electrocatalysis.

[0028] Specifically, the method of using the above catalyst to electrocatalytically oxidize benzyl alcohol or other biomass-derived alcohol organic small molecules is as follows:

[0029] The catalyst powder was dispersed in a mixed solution of water, isopropanol and 5wt.% Nafion solution (the volume ratio of the three solutions was 10:9:1), the mass volume ratio of the catalyst to the mixed solution was 5-30mg / mL, and the catalyst ink was prepared by ultrasonication for half an hour. 100-3000uL of the catalyst ink was dropped on a 1.0*0.5-1.0*2.0cm 2Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, mercury / mercury oxide electrode (Hg / HgO) was used as the reference electrode, 1 mol / L KOH + 0.05-0.2 mol / L substrate (such as benzyl alcohol, methanol, ethanol, ethylene glycol, glycerol, isopropanol, diethylene glycol, furfuryl alcohol, 5-hydroxymethylfurfural, 4-hydroxy-3-methoxybenzyl alcohol, etc.) was used as the electrolyte, and a French Bio-logic EC-LAB electrochemical analyzer was used to perform all electrochemical tests at room temperature, including cyclic voltammetry test, linear voltammetry test, chronoamperometry electrolysis test, etc.

[0030] Compared with the existing technical solutions, the technical solution of the present invention has the following advantages and beneficial effects:

[0031] (1) The catalyst of the present invention adopts the impregnation method and H2 reduction method, which has the characteristics of simple operation and low cost. The obtained catalyst has uniform particle size (average particle size 2.38nm) and good repeatability.

[0032] (2) The catalyst of the present invention is constructed by PtZn-ZnO x The interfacial structure enhances the adsorption and activation of benzyl alcohol and reaction intermediates, and promotes the electrophilic OH * The formation of substances reduces Ph-CHO * With OH * Coupling to generate Ph-C(OH)HO * The energy barrier of the step significantly improves the performance of the catalyst in the electrocatalytic oxidation of benzyl alcohol at a low potential. In some embodiments, the catalyst of the present invention has an initial potential as low as 0.19 V (compared to the reversible hydrogen electrode) in a 1.0 M KOH + 0.1 M Ph-CH2OH electrolyte, and a current density of 126 mA cm at a potential of 0.85 V vs. RHE. -2 , which is twice that of commercial Pt / C.

[0033] (3) The catalyst of the present invention can efficiently oxidize benzyl alcohol to produce benzoic acid in a low potential range (0.6-0.9 V vs. RHE), achieving nearly 100% benzoic acid selectivity and 100% electrocatalytic Faraday efficiency, showing high conversion efficiency and excellent product selectivity.

[0034] (4) The catalyst of the present invention is universally applicable to the oxidation reaction of various biomass-derived alcohol organic small molecules, such as benzyl alcohol, methanol, ethanol, ethylene glycol, glycerol, isopropanol, diethylene glycol, furfuryl alcohol, 5-hydroxymethylfurfural, 4-hydroxy-3-methoxybenzyl alcohol and other organic substances, providing ideas for the design of electrocatalysts for selective activation of CH bonds and value-added conversion of organic small molecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. However, it should be noted that these drawings are designed only for explanation purposes and are not intended to limit the scope of the present invention.

[0036] Figure 1 The PtZn-ZnO prepared in Example 1 of the present invention x High-resolution transmission electron microscopy image of the catalyst.

[0037] Figure 2 The PtZn-ZnO prepared in Example 1 of the present invention x and PtZn-ZnO x The (etched) catalyst was subjected to Fourier transform X-ray absorption fine structure (FT-EXAFS) spectroscopy.

[0038] Figure 3 The PtZn-ZnO prepared in Example 1 of the present invention x 、PtZn-ZnO x (etched) and PtZn-ZnO after 5 cycles of reaction x X-ray photoelectron spectroscopy (XPS) of the catalyst.

[0039] Figure 4 The PtZn-ZnO prepared in Example 1 of the present invention x 、PtZn-ZnO x Linear voltammetric curves of benzyl alcohol oxidation test over (etched) and commercial Pt / C catalysts in alkaline electrolyte (1 mol / L KOH).

[0040] Figure 5 The PtZn-ZnO prepared in Example 1 of the present invention x 、PtZn-ZnO x The product distribution results of the electrolyte sampled and tested after the electrocatalytic oxidation of benzyl alcohol over Pt / C and commercial Pt / C catalysts in an alkaline electrolyte (1 mol / L KOH) at 0.725 V (relative to the reversible hydrogen electrode) using the chronoamperometry method.

[0041] Figure 6 The PtZn-ZnO prepared in Example 1 of the present invention x The catalyst was used to measure the product selectivity and conversion rate of the electrocatalytic oxidation reaction of benzyl alcohol in an alkaline electrolyte (1 mol / L KOH) at different voltages (0.625 V, 0.725 V, 0.825 V relative to the reversible hydrogen electrode) using the chronoamperometry method.

[0042] Figure 7 The PtZn-ZnO prepared in Example 1 of the present invention xThe Faraday efficiency results of the electrocatalytic oxidation of benzyl alcohol over the catalyst were measured in an alkaline electrolyte (1 mol / L KOH) at different voltages (0.625 V, 0.725 V, 0.825 V relative to the reversible hydrogen electrode) using the chronoamperometry method.

[0043] Figure 8 The PtZn-ZnO prepared in Example 1 of the present invention x Catalyst (left) and PtZn-ZnO x Product distribution results of the (etched) catalyst (right) in alkaline electrolyte (1 mol / L KOH) for 5 consecutive cycles of stability testing for the oxidation of benzyl alcohol at a voltage of 0.725 V (relative to the reversible hydrogen electrode).

[0044] Fig. 9 The PtZn-ZnO prepared in Example 1 of the present invention x High-resolution transmission electron microscopy image and element distribution map of the catalyst after cyclic stability testing.

[0045] Fig.10 The PtZn-ZnO prepared in Example 1 of the present invention x Product distribution results of the cyclic stability test of the catalyst for the oxidation of benzyl alcohol in a neutral electrolyte (1 mol / L PBS solution) at a voltage of 0.725 V (relative to the reversible hydrogen electrode) for 5 consecutive times.

[0046] Fig.11 The PtZn-ZnO prepared in Example 1 of the present invention x The catalyst was tested for oxidation reactions of other biomass-derived alcohols and other small organic molecules in alkaline electrolyte (1 mol / L KOH) using linear voltammetry. DETAILED DESCRIPTION

[0047] First, it should be noted that the specific structure, features and advantages of the present invention will be specifically described below by way of example, but all descriptions are only for illustration and should not be understood as limiting the present invention in any way. In addition, any single technical feature described or implied in the embodiments mentioned herein can still be combined or deleted between these technical features (or their equivalents) to obtain more other embodiments of the present invention that may not be directly mentioned herein.

[0048] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0049] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.

[0050] Example 1

[0051] Preparation of PtZn-ZnO x 、PtZn-ZnO x (etched) catalyst

[0052] PtZn-ZnO x Preparation method of the catalyst: zinc oxide powder (80 mg) is impregnated in H2PtCl6·6H2O solution (0.1 g / mL, 0.5 mL) by impregnation method, and the obtained powder is dispersed in tris(hydroxymethyl)aminomethane solution (10 mmol / L, 65 mL) after drying, and stirred evenly to obtain a light yellow suspension. Dopamine hydrochloride (40 mg) is added to the suspension while stirring, and stirred at room temperature for 12 hours to polymerize dopamine. The obtained product is washed with deionized water and ethanol several times, collected by centrifugation, dried in an oven at 60°C, placed in a quartz ark with a lid, and placed in a tubular furnace at 800°C with a hydrogen-argon mixed gas as the protective atmosphere, wherein the hydrogen gas volume fraction is 5%, and treated at a heating rate of 5°C / min for 1 hour to prepare a PtZn intermetallic alloy. The sample is exposed to air for 5 hours to form PtZn-ZnO x .

[0053] PtZn-ZnO x Preparation method of (etched) catalyst: PtZn-ZnO x Place in HNO3 solution (5mmol / L) and stir for 12 hours, centrifuge the obtained sample, wash several times with deionized water, and dry in an oven at 60℃ to obtain the etched product PtZn-ZnO x (etched).

[0054] Figure 1 PtZn-ZnO xThe high-resolution transmission electron microscopy image of the catalyst shows that the catalyst particles expose the (110) crystal plane of the PtZn intermetallic compound, forming a body-centered cubic (bcc) structure of the PtZn intermetallic compound. The average particle size of the catalyst is 2.38 nm. Under the action of the polydopamine layer coating, the migration of Pt atoms and the aggregation of nanoparticles in a high-temperature reducing atmosphere are effectively inhibited. Figure 2 PtZn-ZnO x and PtZn-ZnO x The Fourier transform X-ray absorption fine structure (FT-EXAFS) spectrum of the (etched) catalyst shows a The peaks near the Zn-O bond indicate that PtZn-ZnO x The presence of ZnO in the catalyst x , while the acid-etched PtZn-ZnO x The significant decrease in the Zn-O peak intensity in the FT-EXAFS spectrum of the (etched) catalyst also proves that the ZnO x removal. Figure 3 PtZn-ZnO x and PtZn-ZnO x (etched) and PtZn-ZnO after 5 cycles of reaction x X-ray photoelectron spectroscopy (XPS) of the catalyst shows that PtZn-ZnO x There is Zn 2+ and Zn 0 , further confirming that PtZn-ZnO x ZnO in catalyst x The presence of nitric acid treated PtZn-ZnO x (etched) catalyst surface ZnO x With PtZn-ZnO x The interface is removed.

[0055] Example 2

[0056] PtZn-ZnO prepared in Example 1 x 、PtZn-ZnO x The electrocatalytic oxidation of benzyl alcohol was carried out on Pt / C catalysts (etched) and commercial Pt / C catalysts.

[0057] PtZn-ZnO x As a catalyst: 100uL of catalyst ink (10mg / mL, 0.25wt.% Nafion) was dropped on a 1.0*0.5cm 2Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, mercury / mercury oxide electrode (Hg / HgO) was used as the reference electrode, and 25 mL of 1 mol / L KOH + 0.1 mol / L benzyl alcohol solution was used as the electrolyte. In such a three-electrode system, a linear voltammetric curve test was performed at room temperature using a French Bio-logic EC-LAB electrochemical analyzer. The test results are shown in Figure 4 shown.

[0058] PtZn-ZnO x (etched) as a catalyst: the operation steps are the same as above PtZn-ZnO x As a catalyst step, PtZn-ZnO x Replaced with PtZn-ZnO x (etched), the test results are as follows Figure 4 shown.

[0059] Commercial Pt / C as catalyst: The operation steps are the same as above for PtZn-ZnO x As a catalyst step, PtZn-ZnO x Replaced with commercial Pt / C, the test results are as follows Figure 4 shown.

[0060] Figure 4 PtZn-ZnO x 、PtZn-ZnO x (etched), commercial Pt / C catalyst was tested by linear voltammetry for benzyl alcohol oxidation at room temperature. The results showed that PtZn-ZnO x The catalyst has an onset potential of 0.19 V (vs. reversible hydrogen electrode), which is 160 mV lower than that of commercial Pt / C; at 0.85 V vs. RHE, PtZn-ZnO x The peak current density of BAOR reached 126 mA cm -2 , respectively PtZn-ZnO x (etched) and 1.4 and 5 times that of commercial Pt / C, indicating that PtZn-ZnO x The BAOR reaction activity of PtZn-ZnO x The catalytic performance of PtZn-ZnO x The interface promotes the catalytic activity of benzyl alcohol oxidation reaction.

[0061] Example 3

[0062] PtZn-ZnO prepared in Example 1 x 、PtZn-ZnO x(etched) and commercial Pt / C catalysts were tested for constant voltage products.

[0063] The test conditions are as follows: 3 mL of catalyst ink (10 mg / mL, 0.25 wt.% Nafion) is dropped on a 1.0*2.0 cm 2 Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, mercury / mercury oxide electrode (Hg / HgO) was used as the reference electrode, and 20 mL of 1 mol / L KOH+5 mmol / L benzyl alcohol solution was used as the electrolyte. In such a three-electrode system (H-type electrolytic cell), a French Bio-logic EC-LAB electrochemical analyzer was used to perform a chronoamperometric test at a constant voltage of 0.725 V (relative reversible hydrogen electrode) at room temperature. After testing for 5 hours, 200 μL of the electrolyte was taken, and the obtained electrolyte was neutralized with 2 mol / L hydrochloric acid, and then extracted with ethyl acetate. The supernatant after extraction (100 μL) was added with N,N-dimethylformamide (100 μL), placed in a chromatographic bottle, filtered with a 0.22 μm organic Nylon 66 membrane, and tested and analyzed using a Foley gas chromatograph (GC 9790Plus). The RB-FFAP capillary column (specifications: 0.32 mm ID × 0.25 um Film × 30 m) was selected for analysis with a flame ionization detector, the temperature was set to 300 °C, the injection port temperature was set to 270 °C, and the split ratio was 10:1. The test results are shown in Figure 5 shown.

[0064] PtZn-ZnO x (etched) as a catalyst: the operation steps are the same as above PtZn-ZnO x As a catalyst step, PtZn-ZnO x Replaced with PtZn-ZnO x (etched), the test results are as follows Figure 5 shown.

[0065] Commercial Pt / C as catalyst: The operation steps are the same as above for PtZn-ZnO x As a catalyst step, PtZn-ZnO x Replaced with commercial Pt / C, the test results are as follows Figure 5 shown.

[0066] Figure 5 PtZn-ZnO x 、PtZn-ZnO x (etched), BAOR product distribution results of commercial Pt / C catalyst at 0.725V (relative to reversible hydrogen electrode), the results show that PtZn-ZnO xThe selectivity of the catalyst for benzoic acid is 99.5%, close to 100%, compared with the PtZn-ZnO after etching. x The PtZn-ZnO catalyst has a significant improvement over the commercial Pt / C catalyst (etched) (87.1% benzoic acid selectivity) and the commercial Pt / C catalyst (68.5% benzoic acid selectivity). x The interface promotes the formation of the multi-electron product benzoic acid.

[0067] Example 4

[0068] PtZn-ZnO prepared in Example 1 x The electrolyte after the catalyst was subjected to electrocatalytic oxidation of benzyl alcohol at different voltages (0.625 V, 0.725 V, 0.825 V, relative to the reversible hydrogen electrode) was sampled and the product distribution was detected.

[0069] The test conditions are as follows: 3 mL of catalyst ink (10 mg / mL, 0.25 wt.% Nafion) is dropped on a 1.0*2.0 cm 2 Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, mercury / mercury oxide electrode (Hg / HgO) was used as the reference electrode, and 20 mL of 1 mol / L KOH+5 mmol / L benzyl alcohol solution was used as the electrolyte. In such a three-electrode system (H-type electrolytic cell), a French Bio-logic EC-LAB electrochemical analyzer was used to perform chronoamperometric tests at different voltages (0.625 V, 0.725 V, 0.825 V, relative to the reversible hydrogen electrode) at room temperature. After 5 hours of testing, 200 μL of the electrolyte was taken, and the obtained electrolyte was neutralized with 2 mmol / L hydrochloric acid, and then extracted with ethyl acetate. The supernatant after extraction (100 μL) was added with N,N-dimethylformamide (100 μL), placed in a chromatographic bottle, filtered with a 0.22 μm organic Nylon 66 membrane, and tested and analyzed using a Foley gas chromatograph (GC9790Plus). The RB-FFAP capillary column (specifications: 0.32 mm ID × 0.25 um Film × 30 m) was selected for analysis with a flame ionization detector, the temperature was set to 300 °C, the injection port temperature was set to 270 °C, and the split ratio was 10:1. The test results are shown in Figure 6 shown.

[0070] Figure 6 PtZn-ZnO x The product selectivity and conversion rate of the catalyst for the oxidation of benzyl alcohol at 0.625V, 0.725V, and 0.825V (relative to the reversible hydrogen electrode) are as follows: Figure 7 The electrocatalytic Faraday efficiency results show that PtZn-ZnO xThe selectivity of the catalyst for benzoic acid at low potential (<0.9V) is above 95%, and the electrocatalytic Faraday efficiency can reach 100%. By consulting the literature for comparison, the PtZn-ZnO x The catalyst exhibited the highest selectivity for benzoic acid product at low potential (<0.9 V) that has never been reported.

[0071] Example 5

[0072] PtZn-ZnO prepared in Example 1 x and PtZn-ZnO x The (etched) catalyst was subjected to cycle stability test and product detection.

[0073] The test conditions are as follows: 3 mL of catalyst ink (10 mg / mL, 0.25 wt.% Nafion) is dropped on a 1.0*2.0 cm 2 Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, mercury / mercury oxide electrode (Hg / HgO) was used as the reference electrode, and 20 mL of 1 mol / L KOH+5 mmol / L benzyl alcohol solution was used as the electrolyte. In such a three-electrode system (H-type electrolytic cell), a French Bio-logic EC-LAB electrochemical analyzer was used to perform a chronoamperometric test at a constant voltage of 0.725 V (relative reversible hydrogen electrode) at room temperature. After testing for 5 hours, 200 μL of the electrolyte was taken, and the obtained electrolyte was neutralized with 2 mol / L hydrochloric acid, and then extracted with ethyl acetate. The supernatant after extraction (100 μL) was added with N,N-dimethylformamide (100 μL), placed in a chromatographic bottle, filtered with a 0.22 μm organic Nylon 66 membrane, and tested and analyzed using a Foley gas chromatograph (GC 9790Plus). The RB-FFAP capillary column (specifications: 0.32 mm ID × 0.25 um Film × 30 m) was selected for analysis with a flame ionization detector. The temperature was set to 300 °C, the injection port temperature was set to 270 °C, and the split ratio was 10:1. The test was repeated 5 times using the same test method. The test results are shown in Figure 2. Figure 8 shown.

[0074] Figure 8 PtZn-ZnO x and PtZn-ZnO x The product distribution results of the cyclic stability test of the benzyl alcohol oxidation reaction of the (etched) catalyst in alkaline electrolyte (1 mol / L KOH) at a voltage of 0.725 V (relative to the reversible hydrogen electrode) for 5 consecutive times. The results show that PtZn-ZnO xAfter 5 BAOR cycles, the benzyl alcohol conversion (from 85% to 72%) and benzoic acid selectivity (from 99% to 82%) of the catalyst decreased slightly, while PtZn-ZnO x The (etched) catalyst maintained a relatively stable conversion (about 75%) and selectivity (about 85%) during the five BAOR cycle tests. Fig. 9 PtZn-ZnO x High-resolution transmission electron microscopy and element distribution of the catalyst after the cyclic stability test. The results show that after 5 cycles of testing, the PtZn-ZnO x The average size of the catalyst is about 2.0nm, and there is no obvious agglomeration of nanoparticles. x The surface of the catalyst particles is obviously enriched with Pt, so PtZn-ZnO x The slight decrease in the cyclic stability of the catalyst may be attributed to the x Catalyst surface ZnO x The loss of ZnO leads to the formation of a thin Pt layer on the particle surface similar to pure Pt. x The decay of the catalyst performance and the decay of the performance after 5 BAOR cycles confirmed that PtZn-ZnO x ZnO on the catalyst surface x It is very important to improve the performance and stability of BAOR. x After 5 BAOR cycle tests, although the benzyl alcohol conversion rate and benzoic acid selectivity of the catalyst decreased slightly, they still maintained a relatively high level. x The catalyst has good cyclic stability.

[0075] Example 6

[0076] PtZn-ZnO prepared in Example 1 x The catalyst was subjected to cyclic stability test and product detection under neutral conditions (1 mol / L PBS solution).

[0077] The test conditions are as follows: 3 mL of catalyst ink (10 mg / mL, 0.25 wt.% Nafion) is dropped on a 1.0*2.0 cm 2Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, silver / silver chloride electrode (Ag / AgCl) was used as the reference electrode, and 20 mL of 1 mol / L PBS + 5 mmol / L benzyl alcohol solution was used as the electrolyte. In such a three-electrode system (H-type electrolytic cell), a French Bio-logic EC-LAB electrochemical analyzer was used to perform a chronoamperometric test at a constant voltage of 0.725 V (relative reversible hydrogen electrode) at room temperature. After testing for 5 hours, 200 μL of the electrolyte was taken and extracted with ethyl acetate. The supernatant after extraction (100 μL) was added with N,N-dimethylformamide (100 μL), placed in a chromatographic bottle, filtered with a 0.22 μm organic Nylon66 membrane, and then tested and analyzed using a Foley gas chromatograph (GC 9790Plus). The RB-FFAP capillary column (specifications: 0.32 mm ID × 0.25 um Film × 30 m) was selected for analysis with a flame ionization detector. The temperature was set to 300 °C, the injection port temperature was set to 270 °C, and the split ratio was 10:1. The test was repeated 5 times using the same test method. The test results are shown in Figure 2. Fig.10 shown.

[0078] Fig.10 PtZn-ZnO x The product distribution results of the cyclic stability test of the catalyst for benzyl alcohol oxidation reaction in neutral electrolyte (1 mol / L PBS solution) at a voltage of 0.725 V (relative to the reversible hydrogen electrode) for 5 consecutive times showed that compared with the alkaline electrolyte, the benzyl alcohol conversion rate (100%), the selectivity of benzoic acid (100%) and the yield of benzoic acid (about 50%) of BAOR in neutral electrolyte remained relatively stable during the 5 test cycles. This is because ZnO x and PtZn-ZnO x The interface can remain stable in neutral electrolytes. Compared with Example 6, this result indirectly confirms that PtZn-ZnO x ZnO on the catalyst surface x It plays a vital role in improving BAOR performance and stability.

[0079] Example 7

[0080] PtZn-ZnO prepared in Example 1 x The catalyst was tested for the oxidation reaction of other biomass-derived alcohols and other small organic molecules in an alkaline electrolyte (1 mol / L KOH) using linear voltammetry.

[0081] The test conditions are as follows: 100uL of catalyst ink (10mg / mL, 0.25wt.% Nafion) is dropped on a 1.0*0.5cm 2Carbon paper was used as the working electrode, platinum foil was used as the counter electrode, mercury / mercury oxide electrode (Hg / HgO) was used as the reference electrode, and 25 mL of 1 mol / L KOH + 0.1 mol / L substrate (methanol, ethanol, ethylene glycol, glycerol, isopropanol, diethylene glycol, furfuryl alcohol, 5-hydroxymethylfurfural, 4-hydroxy-3-methoxybenzyl alcohol) solution was used as the electrolyte. In such a three-electrode system, a linear voltammetric curve test was performed at room temperature using a French Bio-logic EC-LAB electrochemical analyzer. The test results are shown in Figure 2. Fig.11 shown.

[0082] Fig.11 PtZn-ZnO x The linear voltammetric curves of the catalyst in the oxidation reaction of other biomass-derived alcohol organic small molecules are compared with the linear voltammetric curves before and after addition. The results show that PtZn-ZnO x The catalyst has good catalytic performance for small organic molecules such as methanol, ethanol, ethylene glycol, glycerol, isopropanol, diethylene glycol, furfuryl alcohol, 5-hydroxymethylfurfural, 4-hydroxy-3-methoxybenzyl alcohol, etc. at low potential, which is reflected in its low starting potential (<0.4V, relative to the reversible hydrogen electrode) and large current density, indicating that the PtZn-ZnO x The catalyst has good universality.

[0083] The above embodiments describe the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production x A method for preparing a catalyst having interfacial active sites, characterized in that: The steps include: (1) taking zinc oxide powder and immersing it in a precursor solution containing platinum ions to obtain a zinc oxide composite that adsorbs platinum ions; (2) dispersing the complex described in step (1) in a tris(hydroxymethyl)aminomethane solution, adding dopamine hydrochloride, and performing a mechanical stirring reaction; (3) obtaining a composite sample coated with a polydopamine layer through filtering, washing, centrifuging and drying; (4) placing the composite sample of step (3) in a tube furnace for high-temperature reduction reaction, cooling to room temperature after reduction, and obtaining a PtZn intermetallic compound supported on nitrogen-doped carbon; (5) exposing the PtZn intermetallic compound described in step (4) to air aging to obtain PtZn-ZnO x catalyst.

2. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1 x A method for preparing a catalyst having interfacial active sites, characterized in that: The mass volume ratio of the zinc oxide to the precursor solution containing platinum ions in step (1) is 25 to 400 mg / mL.

3. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1. x A method for preparing a catalyst having interfacial active sites, characterized in that: The platinum ion-containing precursor solution in step (1) is one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, platinum chloride, platinum acetylacetonate, and tetraammineplatinum nitrate, and the concentration of the platinum ion-containing precursor solution is 0.05 to 0.3 g / mL.

4. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1 x A method for preparing a catalyst having interfacial active sites, characterized in that: The impregnation process of step (1) is as follows: the zinc oxide powder and the precursor solution containing platinum ions are fully mixed and then immersed at room temperature for 12 to 48 hours until they are completely dry.

5. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1 x A method for preparing a catalyst having interfacial active sites, characterized in that: The concentration of the tris(hydroxymethyl)aminomethane solution in step (2) is 5 to 20 mmol / L; the mass ratio of dopamine hydrochloride to zinc oxide powder in step (2) is 0.1 to 3.

6. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1. x A method for preparing a catalyst having interfacial active sites, characterized in that: The dispersion process in step (2) includes ultrasonic mixing and stirring mixing; the mechanical stirring reaction duration in step (2) is 8 to 24 hours.

7. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1. x A method for preparing a catalyst having interfacial active sites, characterized in that: The washing solvent used in step (3) is one of deionized water, anhydrous ethanol and a mixture thereof; the centrifugal speed in step (3) is 5000-10000 rpm, the number of centrifugation is 1 to 3 times, and the time of each centrifugation is 2 to 5 minutes; the drying method in step (3) is oven drying at 60 to 80°C.

8. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production according to claim 1. x A method for preparing a catalyst having interfacial active sites, characterized in that: The conditions for the high-temperature reduction reaction in step (4) are: a hydrogen-argon mixed gas as a protective atmosphere, wherein the hydrogen gas volume fraction is 5-10%, and the temperature is increased to 600-800°C at a heating rate of 5-10°C / min and maintained for 0.5-2 hours.

9. A PtZn-ZnO-rich catalyst for low-potential benzoic acid production obtained by the preparation method according to any one of claims 1 to 8 x Catalysts with active interfacial sites.

10. The PtZn-ZnO-rich catalyst for producing benzoic acid at low potential as claimed in claim 9 x Application of catalysts with active interfacial sites, characterized in that Used for electrocatalytic oxidation of benzyl alcohol, methanol, ethanol, ethylene glycol, glycerol, isopropanol, diethylene glycol, furfuryl alcohol, 5-hydroxymethylfurfural, and 4-hydroxy-3-methoxybenzyl alcohol at a low potential of less than 0.9V.

Citation Information

Patent Citations

  • Catalyst for methanol electrooxidation and preparation method thereof

    CN114976047A

  • Ultra-small stable platinum-cobalt nanoparticle catalyst, and preparation method therefor and use thereof in selective hydrogenation

    WO2024109834A1

  • Electrocatalyst for biomass upgrading and plastic degradation, and preparation method therefor and use thereof

    WO2024229891A1